Pengaruh Kepemimpinan Gender Terhadap Disiplin Kerja dan Organizational Citizenship Behavior (OCB) - Syamsir, Syamsir; Pratama, Gilang Nugraha (Faculty of Social Science, Universitas Negeri Padang, 2024)
Studies on work discipline and Organizational Citizenship Behavior (OCB) in government agencies in relation to gender leadership was still relatively rare in the realm of public administration study in Indonesia, including within the BKPSDM agencies in Sungai Penuh City and Kerinci Regency, Jambi Province, even though the study of this aspect was very important in developing knowledge and practice of public administration among employees, including within the BKPSDM agency as a government agency which should prioritize work discipline. This study aimed to identify how much influence gender leadership had on employee work discipline with OCB as an intervening variable at BKPSDM agencies in Sungai Penuh City and Kerinci Regency. This study was conducted using a quantitative approach. The data were collected through questionnaires as well as documentation data support. The data were analyzed using descriptive statistics in the form of frequency, average, percentage, T-Test, and linear regression. The finding of this study indicated that gender leadership had had significant influences on employee work discipline and OCB variables at BKPSDM agencies in Sungai Penuh City and Kerinci Regency.